Evaluasi dan Desain Ulang Antarmuka Menggunakan Metode User Centered Design (UCD) pada Aplikasi Kampus Kita Tendik - Zaman, Badrus; Nayottami, Inten Bajra; Hariyanti, Eva (J-Icon : Jurnal Komputer dan Informatika, 2024)
The Kampus Kita Tendik application is a mobile-based application developed by Airlangga University to streamline and optimize the performance of Educational Personnel. From a usability perspective, the application exhibits several UI/UX issues, including inconsistent font placement and size, as well as a disorganized profile menu. Consequently, there is a need for research to redesign the application interface, aiming to deliver an intuitive user experience, ease of navigation, and enhanced functionality. The research methodology employed includes User Centered Design (UCD) for application design and System Usability Scale (SUS) for assessing application usability. Twenty respondents, comprising Educational Personnel, were engaged to evaluate both the initial design and the redesigned interface. The outcomes of this evaluation, conducted through UCD, demonstrate a marked improvement in application design quality. This is evidenced by the SUS score of 87.14, awarded an A+ grade, for the redesigned application—a significant increase from the initial SUS score of 65.57, which received a C grade.